Concrete world heritage (2005)
The city of Le Havre, in France, has been included recently in the World Heritage List of Unesco. The destroyed area was entirely rebuilt in concrete after the World War II, by a team of architects and urban planners headed by the French architect Auguste Perret. This particular urban space raises a series of questions from classic to modern urbanism, since it uses an orthogonal grid adjusting itself without trouble to the old scheme. In this article, we will explore the models that have made of this city an unique valid example of the urban planning in the XX century, coming out from a particular form to conceive architecture, reason to a tribute to this great architect: Auguste Perret’s gaze.